Estetyzacja ciała zdeformowanego w działaniach tanecznych z udziałem osób niepełnosprawnych - Grenda, Magdalena (Wydawnictwo Wydziału Nauk Społecznych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
Esthetician of deformed body in dance performances with the participation of disabled persons This article focus on dance companies and dance groups which integrate performers who are physically and mentally fit and those with disabilities, for example: CandoCo Dance Company, StopGAP Dance Company, Integracyjny Teatr Tańca „Kierunek”. In addition, the dance companies not only do performances but also provide dance instruction, workshops or trainings. These groups are consisted of disabled and nondisabled people actively participate in their performances. The majority of people identify dance as a means of educating the public on talents and capabilities of persons with disabilities in the art of performing. The aim of this article is to present, that disability is not a barrier to creativity.
Keywords: integracyjny teatr tańca; estetyzacja ciała; kultura konsumpcyjna; deformacje ciała; niepełnosprawni